Zinc Intakes and Health Outcomes: An Umbrella Review - Li, Jin; Cao, Dehong; Huang, Yin; Chen, Bo; Chen, Zeyu; Wang, Ruyi; Dong, Qiang; Wei, Qiang; Liu, Liangren (Frontiers in Nutrition, 2022)
It is widely accepted that the zinc element is crucial in human beings. Zinc has gained more attention during the COVID-19 pandemic due to its utilization for the treatment and prevention of respiratory tract infections. However, some studies also pointed out that zinc intake might cause unwanted side effects and even be dangerous when overdosed. To reveal the relationship between zinc intake and health outcomes, we performed an umbrella review from human studies. In total, the umbrella review included 43 articles and identified 11 outcomes for dietary zinc intake and 86 outcomes for supplementary zinc intake. Dietary zinc intake in the highest dose would decrease the risk of overall and specific digestive tract cancers, depression, and type 2 diabetes mellitus (T2DM) in adults. Supplementary zinc consumption in adults was linked to an improvement of depression, antioxidant capacity and sperm quality, higher serum zinc concentration, and lower concentration of inflammatory markers. Zinc supplementation in children would reduce the incidence of diarrhea and pneumonia, improve zinc deficiency and boost growth. However, zinc might not decrease all-cause mortality in adults or the in-hospital mortality of COVID-19. And better maternal and neonatal outcomes may not derive from pregnant women who consumed higher or lower doses of zinc supplementation (>20 mg/day and <20 mg/day, respectively). Dose-response analyses revealed that a daily 5 mg increment of zinc would lower the risk of colorectal and esophageal cancer, whereas a large dose of zinc supplementation (daily 100 mg) showed no benefit in reducing prostate cancer risk.